EFFECT OF WORKING CAPITAL AND WORKING CAPITAL TO TURNOVER RETURN ON EQUITY (ROE) TO MANUFACTURING COMPANIES LISTED IN THE STOCK EXCHANGE OF INDONESIA 2004-2007 (EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE) - Hairuddin, Hairuddin (Accounting, 2010)
Working capital and working capital turnover is very important to enhance the ability of the company in obtaining a profit, because the working capital and high levels of turnover that the company can operate and close the expenses and costs in the company. Average Return On Equity (ROE) of manufacturing companies listed on the IDX year 2004-2007 there is enough material up and down due to lack of capital work.The problem which will be revealed in this study were (1) What is working capital influence on ROE?, (2) What is the turnover of working capital affect the ROE?, and (3) Is working capital and working capital turnover is jointly influence on ROE?. The analysis technique used in this study were t-test, F test, and test determination. By using SPSS version 16 obtained the following results: (1) Working capital is not influential to ROE, this can be seen from the t value of -0.694 with a probability of 0.492 error rate significantly exceeds the expected level of 0.050. (2) Capital Turnover work does not affect the ROE, this can be seen from the t value of -0.992 with a probability of 0.328 error rate significantly exceeds the expected value of 0.050. (3) Working capital and working capital turnover is not influential against ROE together, this can be seen from the calculated F value of 0.700 with a probability of 0.503 error rate significantly exceeds the expected level of 0.050. To test the resulting value of determination R Square 0.038 this means the ability of working capital and working capital turnover explain the ROE was 3.8% while the rest equal to 96.2% influenced by other variables in addition to working capital and working capital turnover. Keyword: ROE, Working Capital, Stock Exchage